A novel gyrovirus in a common pheasant (Phasianus colchicus) with poult enteritis and mortality syndrome - Fehér, Enikő; Bali, Krisztina; Kaszab, Eszter; Ihász, Katalin; Jakab, Szilvia; Nagy, Borbála; Ursu, Krisztina; Farkas, Szilvia L.; Bányai, Krisztián (Archives of virology, 2022)
A novel gyrovirus was detected in an intestinal specimen of a common pheasant that died due to poult enteritis and mortality syndrome. The genome of the pheasant-associated gyrovirus (PAGyV) is 2353 nucleotides (nt) long and contains putative genes for the VP1, VP2, and VP3 proteins in an arrangement that is typical for gyroviruses. Gyrovirus-specific motifs were identified in both the coding region and the intergenic region of the PAGyV genome. The VP1 of PAGyV shares up to 67.6% pairwise nt sequence identity with reference sequences and forms a distinct branch in the phylogenetic tree. Thus, according to the recently described species demarcation criteria, PAGyV belongs to a novel species in the genus Gyrovirus , family Anelloviridae , for which we propose the name " Gyrovirus phaco 1 ".